2013
DOI: 10.1371/journal.pone.0083969
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the HMGA1 Gene by Octamer-Binding Proteins Oct-1 and Oct-2

Abstract: The High-Mobility Group AT-Hook 1 (HMGA1) protein is an architectural transcription factor that binds to AT-rich sequences in the promoter region of DNA and functions as a specific cofactor for gene activation. Previously, we demonstrated that HMGA1 is a key regulator of the insulin receptor (INSR) gene and an important downstream target of the INSR signaling cascade. Moreover, from a pathogenic point of view, overexpression of HMGA1 has been associated with human cancer, whereas functional variants of the HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Also, the HMGA1 promoter is activated by the transforming growth factor-β1 (TGF-β1) ( 29 ). Recently, we identified an octamer motif ATGCAAAT at the beginning of exon 1, where the octamer transcription factors Oct-1 and Oct-2 exert a differential regulation of HMGA1 gene transcription, and demonstrated that, by binding its own promoter, HMGA1 can contribute to its transactivation by Oct-2 ( 30 ), thus supporting a previous observation about the role of HMGA1 in an auto-regulatory circuit ( 31 ). More recently, it has been reported that G9a, an activator of gene transcription and a histone methyltransferase, positively regulates the expression of the HMGA1 gene in hepatic cells ( 32 ).…”
Section: General Characteristics Of Hmga1supporting
confidence: 84%
“…Also, the HMGA1 promoter is activated by the transforming growth factor-β1 (TGF-β1) ( 29 ). Recently, we identified an octamer motif ATGCAAAT at the beginning of exon 1, where the octamer transcription factors Oct-1 and Oct-2 exert a differential regulation of HMGA1 gene transcription, and demonstrated that, by binding its own promoter, HMGA1 can contribute to its transactivation by Oct-2 ( 30 ), thus supporting a previous observation about the role of HMGA1 in an auto-regulatory circuit ( 31 ). More recently, it has been reported that G9a, an activator of gene transcription and a histone methyltransferase, positively regulates the expression of the HMGA1 gene in hepatic cells ( 32 ).…”
Section: General Characteristics Of Hmga1supporting
confidence: 84%
“…The Oct-1X is expressed at a low level comparatively to Oct-1A. This is an important fact, since at present time this isoform is considered as a ‘canonical’ Oct-1 sequence and is used in the majority of studies devoted to investigation of Oct-1 functions (14,23,25,4046). …”
Section: Discussionmentioning
confidence: 99%
“…Nuclear protein extracts were prepared as previously [ 29 ] and final protein concentration in the extracts was determined by the modified Bradford method (Bio-Rad Laboratories, Hercules, CA, USA). The antibodies used for Western blot studies were: anti-HMGA1 [ 41 ], anti-FoxO1 (Santa Cruz Biotechnology, Santa Cruz, CA) and anti Sp1 [ 42 ].…”
Section: Methodsmentioning
confidence: 99%